Hypoxia and Integrin-Mediated Epithelial Restitution during Mucosal Inflammation - Goggins, Bridie J.; Chaney, Ciaran; Radford-Smith, Graham L.; Horvat, Jay C.; Keely, Simon (Frontiers in Immunology, 2013)
Epithelial damage and loss of intestinal barrier function are hallmark pathologies of mucosal inflammation associated with conditions such as inflammatory bowel disease. In order to resolve inflammation and restore intestinal integrity, the mucosa must rapidly and effectively repair the epithelial barrier. Epithelial wound healing is a highly complex and coordinated process and the factors involved in initiating intestinal epithelial healing are poorly defined. In order for restitution to be successful, there must be a balance between epithelial cell migration, proliferation and differentiation within and adjacent to the inflamed area. Endogenous, compensatory epithelial signalling pathways are activated by the changes in oxygen tensions that accompany inflammation. These signalling pathways induce the activation of key transcription factors, governing a range of responses, including anti-apoptotic and proliferative processes, which result in epithelial cell survival, proliferation and differentiation at the site of mucosal inflammation. In this review, we will discuss the primary processes involved in epithelial restitution with a focus on the role of hypoxia inducible factor (HIF) and epithelial integrins as mediators of epithelial repair following inflammatory injury at the mucosal surface.